Role of the Faculty of Education in the development of citizenship values among students "A field study from the viewpoint of faculty members at Tishreen University' - Zmourod, Amira; Ahmad, Mutieah (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aimed to investigate the role of the Faculty of Education of Tishreen University in developing the values ​​of citizenship among its students, from the faculty members' viewpoint.The two researchers used the descriptive method, where the survey tool (questionnaire) was distributed to a sample of (52) faculty members of the Faculty of Education. The field study was conducted in December and January/ 2017. Means and standard deviations were used to analyze the data. The study found that the Faculty of Education of Tishreen University plays its role moderately in the development of the values ​​of citizenship of its student. In regard to the sub-themes of the questionnaire, the contribution of university courses and faculty administration was medium, while the contribution of the educational environment and university students' activities was low. The study also confirmed that there are no differences in the viewpoints of the faculty members about the faculty's contribution to the development of the values ​​of citizenship of its students according to gender and study country. The study came to a number of proposals to activate the role of the faculty in developing the values ​​of citizenship.